Multiple Myeloma and Kidney Disease - Daisuke Katagiri; Eisei Noiri; Fumihiko Hinoshita (The Scientific World Journal)
Multiple myeloma (MM) has a high incidence rate in the elderly. Responsiveness to treatments differs considerably among patients because of high heterogeneity of MM. Chronic kidney disease (CKD) is a common clinical feature in MM patients, and treatment-related mortality and morbidity are higher in MM patients with CKD than in patients with normal renal function. Recent advances in diagnostic tests, chemotherapy agents, and dialysis techniques are providing clinicians with novel approaches for the management of MM patients with CKD. Once reversible factors, such as hypercalcemia, have been corrected, the most common cause of severe acute kidney injury (AKI) in MM patients is tubulointerstitial nephropathy, which results from very high circulating concentrations of monoclonal immunoglobulin free light chains (FLC). In the setting of AKI, an early reduction of serum FLC concentration is related to kidney function recovery. The combination of extended high cutoff hemodialysis and chemotherapy results in sustained reductions in serum FLC concentration in the majority of patients and a high rate of independence from dialysis.